EVALUASI PEMBELAJARAN BERBASIS DIGITAL SEBAGAI UPAYA PENINGKATAN KUALITAS PROSES BELAJAR DI SEKOLAH DASAR - Wulanda Febiani; Fatimah Nursyifa’ Setiyono; Viviana Sindy Winata; Khoirina Bilkisti; Ari Shella Sayekti; Delia Indrawati; Ika Febriana Wati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Using digital technology in education is crucial for improving the quality of learning evaluation in elementary schools. This study aims to determine the effectiveness, barriers, and possible ways to utilize digital platforms such as Wordwall, Quizizz, Kahoot, Canva, and YouTube as evaluation tools. The methods used were literature review and development research. The results indicate that digital media can increase students' curiosity, enthusiasm for learning, and achievement because they are more engaging and tailored to their needs. Media such as Wordwall have very high validity and practicality, making them suitable for use. However, several issues remain, such as teachers' limited technological skills, limited internet access, and the potential for cheating during online assessments. Therefore, ongoing teacher training, strengthening digital leadership skills, and better use of learning analytics are needed. In general, digital media can improve learning outcomes if supported by a robust system.